Synthesis, Spectroscopic, and Biological Activity Study for New Complexes of Some Metal Ions with Schiff Bases Derived From 2-Hydroxy Naphthaldehyde with 2-amine benzhydrazide - Mohan, Bushra; Shaalan, Naser (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
This study describes the preparation of tetradentate Schiff base derived from the condensation of 2-Hydroxy naphthaldehyde with 2-amine benzhydrazide and the synthesis of new complexes series with a good yield.The prepared ligand was characterized using a microanalysis technique, UV-visible, FT-IR, nuclear magnetic resonance 1H-NMR, mass spectrometry, thermal gravimetric analysis TGA, and the addition of conductivity measurement and magnetic moment of complexes. The invitro antimicrobial activity of the prepared compounds was tested against  Gram-negative Klebsiella pneumonia, Gram-positive Staphylococcus aureu, and Candida albicans by the agar well diffusion method. The spectroscopy and measurement studies showed that the ligand coordinated with the metal ion as a tetradentate ligand via oxygen and nitrogen, forming an octahedral geometry around it. The ligand and its complexes positively affect the studied microorganisms' Gram-positive and Gram-negative strains and fungi.